The Use of Local Language Constraint-Based in the Pronunciation of Standard English: A Study at Sasaknese Learners of West Nusa Tenggara - Arafiq; Nur Ahmadi; Atri Dewi Aziz; La Ode Alfin Haris Munandar (Journal of English Education Forum (JEEF), 2023)
This study aims to determine the effect of a pronunciation learning model based on phonological constraints of regional languages ​​in pronouncing standard English for Sasak speaking students in West Nusa Tenggara. This research is a quantitative-descriptive designs with an experimental method. The object of this research is the sound of the English language produced by students of Sasak speakers at the English Study Program, FKIP University of Mataram. The research data was obtained using tests (pre-test and post-test). This study used a sample of 15 students who are native Sasak speakers. The instrument used is a pronunciation test which is given before (pretest) and after (posttest) learning is carried out. The test results are then analyzed using simple statistics that can be used to explain the changes before learning and after learning. The results of the analysis are then explained formally by using symbols and pictures and informally by using narration so that the findings of this study can be understood as well as possible. The results of this study indicate that learning pronunciation based on local language phonological constraints is effective in increasing students' awareness in anticipating the influence of local language sounds (mother tongue) in producing English.